PERAN LITERASI DIGITAL DALAM MENANGKAL DISINFORMASI DI ERA KEMAJUAN TEKNOLOGI DAN KETERBUKAAN INFORMASI DALAM PERSPEKTIF TAFSIR AL-QUR’AN KLASIK DAN KONTEMPORER: (Studi Komparasi Tafsir Al-Thabari dan Tafsir Al-Misbah) - Joko Purboyo; Abdur Rokhim Hasan; Kerwanto (Berajah Journal, 2026)
This study concludes that digital literacy plays a vital role in countering disinformation in the era of technological advancement and information openness. Based on a comparative analysis of Tafsir at-Ṭabari (classical) and Tafsir al-Miṣbāḥ (contemporary), both interpretations emphasize the importance of tabayyun (information verification), as found in QS. Al-Ḥujurāt [49]: 6. Tafsir at-Ṭabari stresses the necessity of verifying reports from untrustworthy sources to prevent decisions based on falsehoods, while Tafsir al-Miṣbāḥ contextualizes this principle in the digital age by promoting information filtering, source evaluation, and critical awareness. This conclusion is further reinforced by Jean Baudrillard’s theory of hyperreality, in which truth is often replaced by what becomes viral, rather than factual. F. Budi Hardiman adds that today’s digital society is polarized between two extremes: religious radicalism and post-truth relativism both of which exacerbate the spread of disinformation. Hence, ethical and critically informed digital literacy is essential for safeguarding information integrity and fostering a healthy digital environment. The findings are consistent with previous scholarly works. For instance, Panji Ansari and Abdillah (2022) emphasize the relevance of QS. 49:6 in combating hoaxes through tabayyun, source awareness, and media discernment. Similarly, various Islamic communication studies underscore media literacy and verification as collective efforts against misinformation. These similarities reveal a convergence between Islamic scriptural interpretation and contemporary academic perspectives regarding the urgency of digital literacy to uphold social harmony amid rampant falsehood. Nonetheless, this thesis offers a broader and more interdisciplinary approach than earlier works. Rocky Romansyah (2022), for example, focuses solely on contemporary exegesis without incorporating philosophical frameworks. Muhammad Thaef Ashshiddiqi (2019) adopts a normative-descriptive method without comparing classical and modern tafsir. Likewise, Dwi Putri Aulia’s (2018) study is limited to anti-hoax activism without engaging tafsir or theoretical analysis. This thesis therefore presents a distinct contribution by integrating Qur’anic values with philosophical thought. The methodology employed is qualitative-descriptive using a library research approach with comparative analysis. Primary sources include Tafsir Jāmi‘ al-Bayān by al-Ṭabari and Tafsir al-Miṣbāḥ by Quraish Shihab. Secondary sources involve literature on digital literacy, disinformation, and the works of Jean Baudrillard and F. Budi Hardiman. Analysis was conducted through interpretation of tafsir texts, thematic comparison between classical and modern perspectives, and theoretical integration to formulate an ethical-literary framework for addressing digital disinformation effectively.